1996
DOI: 10.1007/bf01925572
|View full text |Cite
|
Sign up to set email alerts
|

Amylin given by central or peripheral routes decreases gastric emptying and intestinal transit in the rat

Abstract: The effect of rat amylin on gastric emptying and intestinal transit in the rat was examined. Amylin administered intracerebroventricularly (1, 2, 2.5 or 4 micrograms/rat) produced the maximal decrease in gastric emptying and intestinal transit at the dose of 2.5 micrograms/rat. Higher doses produced a lower effect. Peripheral administration (25, 50 or 100 micrograms/kg) produced dose-dependent effects. Pre-treatment with neostigmine blocked the effect of amylin when it was centrally injected, while the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…In experimental models of diabetes the were very similar to those previously described in the rat brain [22,23]. Thus far, the receptors for calcitonin [28], ratio of amylin to insulin mRNA expressed in the -adrenomedullin [29] and two putative CGRP receptors ing [50][51][52] and the regulation of food intake [53][54][55], which may be functionally related [56]. Amylin has also [30,31] have been cloned.…”
Section: Components Of the Amylin System (As)supporting
confidence: 59%
“…In experimental models of diabetes the were very similar to those previously described in the rat brain [22,23]. Thus far, the receptors for calcitonin [28], ratio of amylin to insulin mRNA expressed in the -adrenomedullin [29] and two putative CGRP receptors ing [50][51][52] and the regulation of food intake [53][54][55], which may be functionally related [56]. Amylin has also [30,31] have been cloned.…”
Section: Components Of the Amylin System (As)supporting
confidence: 59%
“…Amylin has also been detected in gut endocrine cells (35), visceral sensory neurons (36), and throughout the brain (44). Exogenous amylin potently reduces food intake (1,3,39), body weight (1), adiposity (41), gastric emptying (10,39), and gastric acid secretion (15) when administered systemically or into the brain. We recently demonstrated that the minimal effective intravenous dose for amylin-induced inhibition of food intake and gastric emptying in rats (1 pmol ⅐ kg Ϫ1 ⅐ min Ϫ1 ) increases plasma amylin by an amount comparable to that produced by a meal (3,39).…”
mentioning
confidence: 99%
“…Several lines of evidence suggest that these peptides may act directly within the brain. 1) Central nervous system (CNS) administration of sCT (13,20), amylin (1,5,10,41), CGRP (20,22,38), and ADM (30) appears to be more potent than systemic administration in reducing food intake and gastric emptying. 2) Subdiaphragmatic vagotomy does not attenuate anorexic responses to sCT (34) and amylin (25,26).…”
mentioning
confidence: 99%
“…Amylin is known to be a potent inhibitor of gastric motility (Young et al, 1996a), an eect that is probably mediated by a central mechanism (Clementi et al, 1996) involving the vagus nerve since subdiaphragmatic vagotomy destroys the response to amylin (Jodka et al, 1996). Thus considering that enhanced gastric motility is an important factor in the pathogenesis of indomethacin and not in EtOH-induced gastric lesions (Takeuchi et al, 1994) and that NEM treatment was shown to decrease gastric motility (Takeuchi et al, 1991) such an eect could also account for the more pronounced protective eect of amylin on indomethacininduced ulcers when the peptide was administered in rats treated with NEM.…”
Section: Discussionmentioning
confidence: 99%